Pentingnya Standar Operasional Prosedur (SOP) dalam Proses Pembuatan Kabel - Muhammad Rafli (Ikatan Da'i Indonesia, 2025)
In an increasingly competitive and dynamic business era, companies are faced with ever-increasing pressure to achieve success. To achieve this goal, operational efficiency, effectiveness and consistency are key. Standard Operating Procedures (SOP) exist as an important instrument in guiding companies towards achieving this. SOPs are written guidelines that detail the steps and procedures that employees must follow in carrying out their daily duties. Implementing good SOPs helps companies ensure that every step taken by employees complies with established standards, reduces the possibility of errors, and improves the quality of the end result. However, awareness of the importance of SOPs is still not widespread among companies, and many have difficulty implementing them effectively. SOPs have a crucial role in improving operational efficiency, reducing the risk of errors, and ensuring compliance with regulations and industry standards. By providing clear guidance to employees, SOPs help in minimizing confusion, speeding up work flow and increasing productivity. Apart from that, SOPs are very important to help maintain the quality of the product being made, because if in the production process the operator does not work according to the SOP the resulting cable product will most likely not be up to par because of the SOP, we have to look at the thickness of the cable insulation and the materials u